Impact of cognitive function on compliance with treatment in heart failure - Beata Jankowska-Polańska; Maria Kuśnierz; Krzysztof Dudek; Joanna Jaroch; Izabella Uchmanowicz (Kazimierz Wielki University, 2017)
In heart failure (HF) patients frailty syndrome and cognitive impairment (CI) affect outcome by decreasing the capability for performing self-care, adhering to the prescribed treatment regimen, monitoring symptoms. The aim was to investigate whether CI affects the compliance to therapeutic regimens. Methods: 170 with HF were included. We employed the Mini Mental State Examination (MMSE), for dementia and the Revised Heart Failure Compliance Scale to assess compliance. Results: CI patients showed lower compliance in all domains: 2.8±1.0 vs 3.3±1.0 (keeping appointments), 2.8±0.9 vs. 3.4±0.9 (pharmaceutical compliance), 0.4±0.8 vs. 1.4±1.2 (regular body weight monitoring), 2.0±1.3 vs. 2.7±1.0 (reduced salt intake), 1.9±1.2vs. 2.9±1.0 (fluid intake restriction), and 0.5±0.8 vs. 1.7±1.1 (regular exercise). Multiple regression analysis showed cognitive function to be an independent predictor for regular body weight monitoring (β=1.223;p<0.001), fluid intake restriction (β=1.081;p<0.001), and regular exercise (β=1.237;p<0.001). In multivariate analysis, the stimulant variables for compliance with HF treatment were: education (β=1.124), being in a relationship (β=2.231), and lack of cognitive impairment (β=0.320); the number of hospitalizations due to HF was identified as a destimulant (β=-0.495). Conclusion: Non-compliance is a major problem in elderly with HF. The cognitive function is an independent contributor to total compliance and to compliance with non-pharmaceutical recommendations. Being in a relationship and education are independent predictors of better compliance, while the number of rehospitalizations due to HF exacerbations is an independent predictor of worse compliance. Early detection of CI may offer an opportunity for intervention and a key strategy for improving clinical outcomes in older adults with HF.